The Effectiveness of Strategic Management of Banking: Statistical Assessment - Kolesnik, Ya. V. (Statistics of Ukraine, 2020)
The analysis in focused on the factors and tendencies at the bank services market, determining the importance and necessity of investigating the issues related with performance enhancement of commercial banks. It reveals that an underlying condition for building a well-established and effective domestic bank system is orientation on satisfying the needs of the real economy and the population in bank products and services of high quality. A study of issues related with practical implementation of the mechanism for performance enhancement of commercial banks in Ukraine becomes necessary in view of the integration of the Ukrainian financial system in the global community in the conditions of the saturated market of financial services, the increasing level of consumer demands and requirements to bank products, the strengthening competition in the bank sector, and the coming of big Western banks with high standards of services to the domestic market. All the factors with impact on the commercial bank performance should be taken into account in elaborating tools, processes and actions embedded in the mechanism for performance enhancement of banking. The main phases of strategic management are highlighted. A comparative analysis of the main strategies of the commercial banks operating on the financial market of Ukraine is made. The dynamics of indicators measuring the structure of the banks’ resource base is analyzed. The phases of strategic management of the commercial bank operation and ways of improving the performance enhancement mechanism based on client orientation are discussed. The core tendencies and dynamics of interest rates on loans are analyzed. It is emphasized that the domestic bank market is characterized by low quality and concentration of assets. The inevitable process of market consolidation will widen the opportunities for larger market agents, on the one hand, and increase the competition, on the other hand, which will have favorable effects for quality parameters of the bank system as a whole. Results of the analysis of the current performance of the bank sector in Ukraine enabled the author to highlight main tendencies with impact on the commercial bank performance. The financial results of the bank’s operation and its capabilities to increase investment in the domestic economy and widen the range of services to clients are largely conditional on ways, terms and costs of raised funds, and on the size of bank’s own assets and the structure of bank’s resources.